Pruritus in allergy and immunology - Yang, Ting-Lin B.; Kim, Brian S. (Journal of allergy and clinical immunology, 2019)
Although evolutionarily conserved to expel ectoparasites and aid in the clearance of toxins and noxious environmental stimuli from the host, the type 2 immune response can become pathologic in the setting of a variety of allergic disorders. Itch can be a behavioral extension of type 2 immunity by evoking scratching and, in the setting of disease, can become chronic and thus highly pathologic as well. Classically, our understanding of itch mechanisms has centered around the canonical IgE–mast cell–histamine axis. However, therapies aimed at blocking the histaminergic itch pathway have been largely ineffective, suggesting the existence of nonhistaminergic itch pathways. Indeed, recent advances in itch biology have provided critical new insight into a variety of novel therapeutic avenues for chronic itch in the setting of a number of allergic disorders. Here we highlight how these new developments will likely inform the problem of pruritus in a variety of well-established and emerging conditions in the field of allergy.